Vanillin Schiff bases: Molecular interactions in methanol and THF solutions (2017)
Density, ultrasonic velocity and viscosity of some vanillin Schiff bases derivativeshave been studied in methanol and tetrahydrofuran (THF) at 308.15 K. From theexperimental data, various acoustical parameters such as isentropic compressibility(κs), Rao’s molar sound function (Rm), Van der Waals constant (b), relaxation strength(r), intermolecular free length (Lf), apparent molar compressibility, etc. have beenevaluated, which helps in understanding the molecular interactions occurring inthese solutions